Value polarization in a Norwegian context? Distance between the elite and the population in attitudes toward immigration and gender equality - Midtbøen, Arnfinn H.; Teigen, Mari (Politica, 2019)
To what extent do the Norwegian elite and the population at large differ in their views on immigration and gender equality? The article analyzes data from the Norwegian Leadership Survey 2015, conducted among the holders of top positions in ten sectors in Norwegian society, and compares elite attitudes to attitudes in the Norwegian population. We find a considerable distance between elite and population, but immigration is more polarizing than gender equality. The findings are discussed in light of recent comparative research on populism and the growing resistance to liberal and post-material values, as well as literature on gender equality as a “Nordic value”.